Physicochemical And Antibacterial Properties Of Calamansi Lime And Pandan Leaf Essential Oil Nanoemulsions - Leong, Suet Wen (Universiti Sains Malaysia, 2021)
In this study, the physicochemical properties including particle size, polydispersity index (PDI), particle size distribution, zeta potential, turbidity, viscosity and morphology, as well as antibacterial activity of calamansi lime (Citrofortunella microcarpa) and pandan leaf (Pandanus amaryllifolius) EO nanoemulsions prepared using spontaneous emulsification method were investigated.